Eemian interglacial reconstructed from a Greenland folded ice core - Dahl-Jensen, Dorthe; Albert, M. R.; Aldahan, A.; Azuma, N.; Balslev-Clausen, D.; Baumgartner, M.; Berggren, A.-M.; Bigler, M.; Binder, Tobias; Blunier, T.; Bourgeois, J. C.; Brook, E. J.; et al. (Nature, 2013)
Efforts to extract a Greenland ice core with a complete record of the Eemian interglacial (130,000 to 115,000 years ago) have until now been unsuccessful. The response of the Greenland ice sheet to the warmer-than-present climate of the Eemian has thus remained unclear. Here we present the new North Greenland Eemian Ice Drilling (‘NEEM’) ice core and show only a modest ice-sheet response to the strong warming in the early Eemian. We reconstructed the Eemian record from folded ice using globally homogeneous parameters known from dated Greenland and Antarctic ice-core records. On the basis of water stable isotopes, NEEM surface temperatures after the onset of the Eemian (126,000 years ago) peaked at 8 ± 4 degrees Celsius above the mean of the past millennium, followed by a gradual cooling that was probably driven by the decreasing summer insolation. Between 128,000 and 122,000 years ago, the thickness of the northwest Greenland ice sheet decreased by 400 ± 250 metres, reaching surface elevations 122,000 years ago of 130 ± 300 metres lower than the present. Extensive surface melt occurred at the NEEM site during the Eemian, a phenomenon witnessed when melt layers formed again at NEEM during the exceptional heat of July 2012. With additional warming, surface melt might become more common in the future.
Gesehen am 02.06.2021